Attitudes and perceptions of GPs and community pharmacists towards their role in the prevention of bisphosphonate-related osteonecrosis of the jaw: a qualitative study in the North East of England. Issue 9 (29th September 2017) - Sturrock, Andrew; Preshaw, Philip; Hayes, Catherine; Wilkes, Scott
Abstract : Background: Bisphosphonate-related osteonecrosis of the jaw (BRONJ) is a rare, yet significant, adverse effect of bisphosphonate therapy. A multidisciplinary approach to the prevention of BRONJ is recommended due to the significant morbidity and difficulty treating the condition. Current evidence suggests that both general practitioners (GPs) and community pharmacists have limited knowledge relating to BRONJ and that preventative strategies are rarely implemented. Objective: To explore the attitudes and perceptions of GPs and community pharmacists on the risks and preventative strategies for the development of BRONJ. Design: Interpretivist methodological approach using qualitative semistructured interviews. Participants: 9 community pharmacists and 8 GPs. Setting: Primary Care in North East England and Cumbria, UK. Methods: Using a Grounded Theory methodology and integrating a process of constant comparison in the iterative enrichment of data sets, semistructured interviews were undertaken, transcribed and analysed using framework analysis. Salient themes were identified and related back to extant literature in the field. Results: Four salient and inter-related themes emerged: (1) uncertain knowledge, indicating limited exposure of respondents to BRONJ, and limited awareness of the implications of its diagnosis, risk factors and preventative strategies; (2) patient specific, referring to the complexity of patients, patient education and prioritising aspects of care; (3) wider context, indicating a lack of interdisciplinary communication and referral processes between professions, workload pressures, access and patient receptivity to dental services; and (4) professional, reflecting professional roles and responsibilities, authority and educational initiatives Conclusions: Effective communication or collaborative care between GPs and community pharmacists for the prevention of BRONJ is not apparent. Interventions to mitigate against the risk of developing BRONJ and clarity of GP and community pharmacy roles are required.